Workaholism and Affect: The Moderating Role of Mindfulness - Bellows, Gerald (East Carolina University, 2018)
In the current study we sought to examine the relationships among workaholism, mindfulness, and negative affect. Workaholism is compulsively working excessively hard and is related to detrimental outcomes to both the employee and the organization. Therefore, it is vital that researchers target dispositional driving forces of workaholism to help mitigate its potential harm. As such, in the current study we utilized self-report measures to establish whether dispositional mindfulness had the ability to weaken the relationship between workaholism and negative affect. The sample consisted of working adults from various occupations and backgrounds. The results indicated that workaholism was positively correlated with negative affect, supporting previous research. Dispositional mindfulness was negatively correlated with negative affect, and workaholism was negatively correlated with dispositional mindfulness. The results also demonstrated that mindfulness moderated the relationship between workaholism and negative affect. Organizational implications, limitations, and future directions are discussed.
Keywords: Workaholism--Analysis; Mindfulness (Psychology)